DIGITAL LEARNING RESOURCE AT MA’HAD ‘ALY IDRISIYYAH TASIKMALAYA: AVAILABILITY, ATTITUDE, AND UTILIZATION - Husen Hasan Basri; Saifudin Asrori (UIN Syarif Hidayatullah Jakarta, 2022)
Abstract. Ma’had ‘aly is the education of Islamic boarding school at state higher education organized by the Islamic boarding school and located in their environment with developing Islamic studies by the uniqueness of the Islamic boarding school based on the yellow book in stages and a structured manner. This article discussed the resource of digital learning at Ma’had ‘Aly Idrisiyyah, the availability, attitude, and utilization of digital learning resources. This article used qualitative studies and field observations. Then, this article concludes that the digital learning resource at Ma’had ‘Aly Idrisiyyah modified learning resource in the resource of digital learning, by digitalization from existing learning resources, that is from the attitudes of academic civitas at Ma’had Aly. The utilization of Ma’had ‘Aly Maktabah Idrisiyyah and references of Ma’had ‘Aly Iddrisiyyah.Abstrak. Ma’had ‘aly adalah pendidikan pesantren jenjang pendidikan tinggi yang diselenggarakan oleh pesantren dan berada di lingkungan pesantren dengan mengembangkan kajian keislaman sesuai dengan kekhasan pesantren yang berbasis kitab kuning secara berjenjang dan terstruktur. Artikel ini membahas sumber belajar digital di Ma’had ‘Aly Idrisiyyah yaitu ketersediaan sumber belajar digital, Sikap terhadap sumber belajar digital; dan pemanfaatan sumber belajar digital. Melalui kajian kualitatif dan observasi lapangan, artikel ini menyimpulkan bahwa sumber belajar digital di Ma’had ‘Aly Idrisiyyah, bahwa modifikasi sumber belajar menjadi sumber belajar digital, melalui proses digitalisasi sumber-sumber belajar yang ada, yakni dari sikap para civitas akademi ma’had aly. Pemanfaatan warga Ma’had Aly Maktabah Idrisiyyah dan Pustaka Ma’had Aly Idirisiyyah.